A Survey On Importance Of Routing Protocol In WSN - Bhattacharya, Manasija (The journal of contemporary issues in business and government, 2020)
Many novel protocols specifically intended for sensor networks where energy awareness is an important concern have emerged as a result of recent improvements in wireless sensor networks. The routing protocols, on the other hand, have gotten the most attention because they might alter based on the application and network architecture. This research examines modern sensor network routing protocols and assigns a classification to the various methodologies taken. Data-centric, hierarchical, and location-based are the three key types examined in this paper. These networks are made up of a huge number of tiny devices known as sensor nodes. The sensor nodes connect with one another using a variety of wireless communication methods. Routing protocols are in charge of these communication mechanisms. This research examines modern sensor network routing protocols and assigns a classification to the various methodologies taken. Data-centric, hierarchical, and location-based are the three key types examined in this paper. WSNs are defined by denser node deployment, increased sensor node unreliability, and severe power, compute, and memory constraints. Various design issues for routing protocols in WSNs are highlighted, including energy efficiency, data delivery models, quality of service, overheads, and so on.